The EFFECTS OF AGE ON GROWTH, COMPOSITIONS AND QUALITY ATTRIBUTES OF CHEVON FROM WEST AFRICAN DWARF (GOATS) BUCKS: Introduction - Ayanniyi, N. N.; Adeyemi, S. A.; Eze, J. N.; Aliyu, E. J.; Orimogunje, A. D. (BADEGGI JOURNAL OF AGRICULTURAL RESEARCH AND ENVIRONMENT, 2023)
Abstract Fifty-six growing bucks purchased from different farmers in Oyo and Osun States were used to carry out the study. The animals were weighed and disinfected against both ecto and endo parasites before the start of the experiment. The average weights at purchased ranged between 7.67 and 9.86kg and the experiment laid out in a Complete Randomized Design (CRD). The ages of the bucks were identified and determined using appearance of the incisors and were grouped accordingly. Final Body Weight (FBW), Average Daily Weight gain, (ADWG) and Feed Conversion Ratio, (FCR) were determined using standard procedures. Dressing percentage (DP), Shear Forces (SF), Rib eye area, (REA) and Water holding capacity, (WHC) were evaluated after three bucks per treatments were sacrificed. Also evaluated were percentage proportion of lean, bone and fat. Results showed that the average weights at slaughter were 13.47kg, 16.09 and 20.35kg at 12, 18 and 24 months respectively. However the shear forces of 4.97kg/cm and 5.01kg/cm at 18 and 24 months old bucks were similar and significantly higher than that of yearling goats (2.66 kg/cm). The TFD and MBR also varied significantly as the age. The study concluded that older animals produced carcasses with higher total fat deposits, more meat and but relatively less GI tract contents compared with others. The study recommended however that the cost of managing the animals within a time taken, feed consumptions including medications to reach the 24 month could be economically evaluated to justify the need for the added time.